2012
DOI: 10.1111/j.1468-2273.2012.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Does On‐line Distance Higher Education Pay Off for Adult Learners? The Case of the Open University of Catalonia

Abstract: The increasing opportunities created for adults by on‐line distance universities raise important issues about the payoff to such education. This study uses a unique set of survey data gathered by the Open University of Catalonia (UOC) in 2009 to estimate the earnings gains of the 2000–2003 cohorts of UOC students in six programmes of study over an average six‐year time frame between entering and one year after leaving their studies. It compares their gains with the earnings gains of comparable full‐time worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…As we showed in our earlier study (Carnoy et al 2012b) and confirm with more detailed earnings data here, the earnings effect of a UOC degree or having completed coursework at UOC may be relative small but may bring less educated (especially older) employees' credentials into line with an already high salary. Former and current students in our survey were asked what they expected from their UOC education.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…As we showed in our earlier study (Carnoy et al 2012b) and confirm with more detailed earnings data here, the earnings effect of a UOC degree or having completed coursework at UOC may be relative small but may bring less educated (especially older) employees' credentials into line with an already high salary. Former and current students in our survey were asked what they expected from their UOC education.…”
supporting
confidence: 90%
“…In our previous study of UOC earnings (Carnoy et al 2012b), we also controlled for students' previous education and their parents' education in order to test whether these factors influenced the payoffs to different programs because of self-selection of students into those programs. The coefficients changed minimally when we added these variables, and this was also the case with this second follow-up sample.…”
Section: Estimating the Effect Of Study Program On Earnings Using Regmentioning
confidence: 99%
“…Choi and colleagues' article also suggests that, although adults (and particularly women) initially perceive their enrolment in DE programmes as an opportunity to pursue their study while overcoming immediate socioeconomic barriers and balancing family and study commitments, family and work responsibilities tend to remain a major and unsettled obstacle to their successful completion of the programmes. Similar studies that focus on adult student drop-out consistently suggest that a lack of time for studying (Carnoy, et al, 2012) and a failure to balance academic workload with other life obligations (Vergidis & Panagiotakopoulos, 2002) as the more important factors underlying low completion rates.…”
Section: Motivation and Drop-outmentioning
confidence: 73%
“…), have strong aspirations for pursuing their university degrees. It is suggested, furthermore, that these students are highly motivated to study and to optimise their second opportunities: even when earning the degree provides little in the way of economic benefits (Castaño-Muñox, Carnoy, & Duart, 2016;Carnoy et al, 2012). There have also been studies investigating adult learners' self-reported needs for participation in DE in more specific terms: Raghavan and Kumar (2007), for example, report that the most prevalent need among adult learners at the Open University Malaysia is for professional advancement, followed by cognitive interest and communication improvement, while the least prevalently identified needs related to aspects of escapism and social stimulation; Mulenga and Liang (2008), similarly, report that the strongest motivational factors underlying older adults' participation in DE are related to intellectual stimulation, keeping up, fulfilment, and adjustment, whereas the least important factors are related to escape or social contact.…”
Section: Motivation and Drop-outmentioning
confidence: 99%
See 1 more Smart Citation